Knowledge management in the context of franchising: A case study in a franchise - Menegassi, Cláudia Herrero Martins; Tenório Junior, Nelson Nunes; Sartori, Rejane; Jorge, Carlos Francisco Bitencourt [UNESP] (My University, 2019)
Taking on a franchise requires constant innovation from the franchisor in business processes to make the business sustainable, and in that sense knowledge management is a strategic elements for the best use of organizational knowledge. Thus, the present work aims to propose knowledge management actions as a management strategy in the context of the franchises. The present research, conducted in a franchise, is of applied nature with exploratory objective. The data were collected through structured interview and direct observation. As a result of the research, the points of improvement in the franchise were identified and the knowledge management practices were suggested to improve them and to strengthen the strengths. In addition, it is identified the possibility of the failing to build knowledge in a collaborative way through the use of knowledge management practices, making knowledge available and accessible and thus forming a true knowledge network in the context of franchising.
La gestión del conocimiento en el contexto del franchising: Un estudio de caso en una franquiciada
A gestão do conhecimento no contexto do franchising: Estudo de caso em uma franqueada
Keywords: Entrepreneurship; Franchises; Knowledge management